(3LGeY GdHjGf Yf JChjd GdbQBfs - (3eMeO Hf LQjQ Hf jRjO GdWHQj , GHf LQjQ, CHh LYaQ, J (B310 (3g` s
(3ChdgG (B:s
(3Gdbhd ai JChjd bhdg Ld bVGDg, hGP bGd ehSi daJGg dG CNQL MJi s
(3BNQgG (B:s
(3JeJ GdfSNI HMeO Gddg hYhfg jJdhg JaSjQ ShQI eQje s
(3bWYI efgs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B69 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B147s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA GdChd (B- ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B437s
(3eUOQ GbJfGA GdCUd (B:s
(3GdeZQH (B- (3GdQHGW (B- (3LGeYI GdbQhjf (B- (3aGS (B(74) s
Keywords: (3GdJaSjQ hYdhe GdbQBfs